TATA RITUAL DALAM PROSESI ADAT BUBAK KAWAH DI KECAMATAN GUDO KABUPATEN JOMBANG - Imamah, Muhibatul; M. Basir, Udjang Pairin; Fadli, Rusli Ilham (STKIP PGRI Jombang, 2020)
Language shows that the existence of language and society cannot be separated. Language is also said to be a human communication tool used when voicing information in the form of intentions and thoughts and feelings directly. Like the language and meaning contained in the Ritual Ceremony in the Bubak Kawah Traditional Procession in Gudo, Jombang Regency. The language used in the ceremony is Javanese, each of which has its own meaning. Research at the Bubak Kawah traditional ceremony uses a qualitative approach and is also crossed with a Semiotic Study. The Semiotic study in this research is one which semiotic itself is divided from signs, symbols and meanings. In the procession of Bubak Kawah traditional ritual, which is led by the Bubak Dukon, it uses Javanese language and contains its own prayers and meanings for its followers. The ritual arrangement at the ceremony is held on the morning before noon 05, December 2019 in which all processions will be guided by the shaman bubak and will be followed by the empun hajat. As for the ritual arrangements at the Bubak Kawah traditional ceremony, this was only performed by the empun hajat who was the first to his first daughter. The data source obtained from the researcher is a case of video and data transcripts containing the procession during the Bubak Kawah traditional ritual. Data collection techniques carried out by researchers in the form of video recordings, transcripts and interviews. Data collection procedures performed by researchers include the determination of objects, data collection by audi-visula and data transcript.